Architecture as civil commitment : Lucio Costa's modernist project for Brazil - Piccarolo, Gaia (Abingdon, Oxon ; New York : Routledge, 2020)
"Architecture as Civil Commitment analyzes the many ways in which Costa shaped the discourse of Brazilian modern architecture, tracing the roots, developments, and counter-marches of a singular form of engagement that programmatically chose to act by cultural means rather than by political ones. Split into five chapters, the book addresses specific case-studies of Costa's professional activity, pointing at his multiples role in the Brazilian federal government and focusing on passages of his work that are much less known outside of Brazil, such as his role inside Estado Novo bureaucracy, his leadership at SPHAN, and his participation at UNESCO's headquarter project, all the way to the design of Brasilia. Digging deep into the original documents, the book crafts a powerful historical reconstruction that gives the international readership a detailed picture of one of the most fascinating architects of the 20th century, in all his contradictory geniality. An ideal read for those interested in Brazilian modernism, students and scholars of architectural and urban planning history, socio-cultural and political history, and visual arts"--
The start of a militant career : the direction of the School of Fine Arts -- Reasons of the new architecture : Gustavo Capanema's grands travauxs -- A programme for national architecture : the years of the Estado Novo -- A strategy of mediation : between the CIAM and the SPHAN -- Shaping the true Machine Age : art, city, landscape.
OCLC-licensed vendor bibliographic record.
Keywords: Costa, Lúcio -- Criticism and interpretation; Architecture and society -- Brazil -- History -- 20th century; ARCHITECTURE / General